(untitled) (Anwer Khan Modern Medical College Journal, 2011)
Diagnosis of acute appendicitis in children with equivocal signs is often difficult requiring admission for observation, many of whom are finally discharged because they do not have appendicitis. This study was designed to see whether Alvarado score can aid in diagnosis of acute appendicitis. 71 children with age in between 5-15 were scored. The decision of surgery was made independent of the score. Appendicitis was confirmed in operated cases on operative and on histopathological findings. It was found that patients with low score have little chance to suffer from acute appendicitis. Therefore Alvarado scoring system can be used in taking decision in the diagnosis of acute appendicitis in children. Key Words: Acute Appendicitis; Alvarado Score DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8165 AKMMC J 2011; 2(2): 11-13